Zakat Fund Distribution Innovation for Beneficiaries in Tangerang Regency - Tolkah (LEGAL BRIEF, 2021)
Welfare is an ideal that is desired by all citizens and also humankind in all corners of the world, including those desired by all the people of the Republic of Indonesia. The purpose of welfare for all people in a country is to ensure equitable justice for every citizen of its country, as well as development that occurs in a religious field. which can increase the participation of religious communities in realizing the formation of national development. As the majority community in Indonesia, Muslims must be able to have a significant impact in the provision and empowerment of zakat funds for all groups of zakat recipients in Indonesia. The potential for zakat funds available in Indonesia is very large, as well as the potential for zakat that is owned by the Tanggerang Regency area which reaches 20 billion. If the muzaki and groups of zakat recipients in the Tangerang City area are aware of the amount of available zakat funds and are aware of the obligation to pay zakat, the management and distribution of zakat funds can also be more channeled and more evenly organized. With the participation of an institution that manages zakat funds such as BAZNas in Tanggerang Regency, zakat management is more optimal. From the background mentioned, there is a research question related to the above problem, namely: What method is used by the Tanggerang National Zakat Agency (BAZNas) in distributing zakat maal funds. The methodology used in this research is a case study method with a qualitative approach. Data collection techniques used are observation, interviews and documentation. The results of this study show that the distribution method used by the National Zakat Agency (BAZNas) of Tanggerang Regency is a consumptive and productive distribution method, the data collection techniques used are observation, interviews and document analysis techniques.